The blue banner : the Presbyterian Church of Saint David and Presbyterian witness in Halifax - Cahill, Barry (Published for Presbyterian Church of Saint David by McGill-Queen's University Press, 2008)
On 10 June 1925, the date the United Church of Canada was founded, two-thirds of the congregations of the Presbyterian Church of Canada - including every Presbyterian congregation in Halifax - vanished. Even before the United Church came into existence, however, non-uniting Presbyterians were forming a new congregation.